تجارتی معاملات میں "حقوق" بطور مبیع (مؤلف، موجد اور ناشر کے حقوق کی خرید وفروخت کے بارے میں فقہی اکادمیات کے قراردادوں کا تجزیاتی مطالعہ): “RIGHTS” AS SUBJECT MATTER OF SALE IN COMMERCIAL TRANSACTIONS (AN ANALYTICAL STUDY OF FIQH ACADEMIES' RESOLUTIONS ON THE SALE AND PURCHASE OF AUTHORS', INVENTORS', AND PUBLISHERS' RIGHTS) (Contemporary Journal of Social Science Review, 2025)
Throughout history, humans have exchanged goods to meet primary and secondary needs, and trade (tijārat) has remained the most enduring mechanism. In a sale contract (ʿaqd bayʿ), the parties mutually agree to transfer both the commodity (mabīʿ) and its price (thaman). To prevent commercial malpractices, disputes, and conflicts in commercial dealings, Islamic Sharīʿah has systematically established fundamental principles, regulations, and conditions (qawāʿid wa sharāʾiṭ) governing such transactions.The contract of sale (ʿaqd al-bayʿ) encompasses numerous sub-categories, among which the legal rulings and conditions pertaining to the subject matter of sale (mabīʿ) constitute a significant jurisprudential domain. Classical Islamic jurists (fuqahāʾ) have meticulously delineated specific conditions for the mabīʿ in their legal compendiums, establishing criteria for determining which commodities are eligible for commercial exchange and which are prohibited from becoming objects of sale.In contemporary commercial practice, alongside the traditional exchange of tangible assets and corporeal goods (aʿyān), transactions involving intangible or incorporeal entities have gained prominence. Among these emerging commercial phenomena, the sale and purchase of "rights" (ḥuqūq) represents a particularly significant development. This emergence raises fundamental jurisprudential questions regarding the legitimacy of trading rights as commodities under Islamic commercial law: Are rights permissible as subjects of sale? Which categories of rights may constitute valid objects of commercial exchange, and which are prohibited?Among these tradeable rights are intellectual property rights including authorial rights (ḥuqūq al-muʾallif), inventors' rights (ḥuqūq al-mukhtariʿ), and publishers' rights (ḥuqūq al-nāshir), which are actively traded in contemporary markets. This article examines these specific categories of intellectual property rights, investigating the scope of rights accorded to authors, inventors, and publishers under Islamic jurisprudence. Furthermore, it analyzes the perspectives of national governments, international organizations, and Islamic juridical academies (al-majāmiʿ al-fiqhiyyah) established for collective ijtihād regarding the commercial exchange of such intellectual property rights within the framework of Islamic commercial law.